Skilled Speaking Students at Ulil Albaab Islamic Boarding School East Lombok - Pahrurrozi, Muhammad; Hersulastuti, Hersulastuti; Kholid, Kholid (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to examine the teaching and learning of speaking skills at the Ulil Albaab Islamic Boarding School in the 2023/2024 academic year, with an emphasis on the reasons for and practices of its implementation. This study uses a qualitative case study approach with data collection through observation, in-depth interviews with teachers and students, and document analysis. The results show that speaking skills learning is dominated by a communicative approach that utilizes group discussion, presentation, and simulation strategies to encourage the use of language in real contexts. This approach is capable of creating an interactive learning atmosphere, despite facing challenges such as limited resources, varying levels of student confidence, and limited vocabulary mastery. Nevertheless, the integration of practice-based methods continues to play an important role in improving students' speaking skills. These findings have implications for the development of strategies for teaching speaking skills in Islamic boarding schools and similar educational institutions.